Artificial Intelligence Responsiveness in Nursing - Areej Al-Hamad; Yasin M. Yasin; Lujain Yasin (Advances in Nursing Science, 2026)
Artificial intelligence (AI) responsiveness in nursing was conceptually analyzed to clarify its defining attributes, antecedents, consequences, and empirical referents. Guided by Walker and Avant’s approach, sources on AI literacy, responsiveness, and related nursing concepts were thematically synthesized. Four defining attributes were identified: foundational understanding of AI, critical appraisal of AI outputs, ethical and accountable response, and integration with clinical judgment. Antecedents included exposure to AI-enabled tools, digital and informatics foundations, education and training, and organizational and regulatory support. AI responsiveness supports safer practice, stronger decision-making, ethical care, equity, readiness, and professional nursing accountability.